Building Performance Through Work Discipline Influenced By Leadership and Compensation - Paijan, Paijan; Jubaedah; Agung Hudaya; R. Joko sugiharjo (Dinasti International Journal of Management Science, 2024)
This research aims to examine and analyze the influence of work discipline, leadership, and compensation in Jakarta. The research design adopts a quantitative approach. The sample selection method involves professionals working in the Jakarta area, utilizing purposive sampling technique with 100 respondents, to be analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The research topic has been aligned with RIP UMB 2021-2024, and the current study refers to several previous research findings, incorporating relevant topics and literature. The research implementation begins with the measurement of the Technology Readiness Level, which is at level 3 with the criteria of proof-of-concept, demonstrating the analytical functionality and/or essential characteristics. The significance of conducting this research is grounded in various relevant references, indicating that the performance level across all sectors, both public and private, especially in the business sector, experiences fluctuations. Therefore, the researcher proposes factors that are considered crucial for employees in terms of performance. These factors are indicated to be work discipline, leadership, and compensation.